2021
DOI: 10.1039/d1sc00140j
|View full text |Cite
|
Sign up to set email alerts
|

Rational designing of glyco-nanovehicles to target cellular heterogeneity

Abstract: Heparan sulfate oligosaccharide based nanovehicle greatly enhance the selective targeting of cancer cells in tumor microenvironment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The synthesis of I tetrasaccharides is not straightforward because IdoA is not commercially available and stereoselective α‐glycosylation between GlcN and IdoA is difficult. I tetrasaccharides synthesis relied on the synthesis of tetrasaccharide precursor 14 from the disaccharides 12 and 13 via deacetylation, oxidation, lactonization, azide reduction and N‐acetylation as was previously described [7,27] . Nap/TBDMS orthogonality was used to access all three I tetrasaccharides from tetrasaccharide 14 via sequential deprotection and sulfation steps (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of I tetrasaccharides is not straightforward because IdoA is not commercially available and stereoselective α‐glycosylation between GlcN and IdoA is difficult. I tetrasaccharides synthesis relied on the synthesis of tetrasaccharide precursor 14 from the disaccharides 12 and 13 via deacetylation, oxidation, lactonization, azide reduction and N‐acetylation as was previously described [7,27] . Nap/TBDMS orthogonality was used to access all three I tetrasaccharides from tetrasaccharide 14 via sequential deprotection and sulfation steps (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…I tetrasaccharides synthesis relied on the synthesis of tetrasac- Chemistry-A European Journal charide precursor 14 from the disaccharides 12 and 13 via deacetylation, oxidation, lactonization, azide reduction and N-acetylation as was previously described. [7,27] Nap/TBDMS orthogonality was used to access all three I tetrasaccharides from tetrasaccharide 14 via sequential deprotection and sulfation steps (Scheme 2). The removal of TBDPS from 14 afforded the O-6 free tetrasaccharide 15, which following sulfation afforded O-6 sulfated tetrasaccharide 17.…”
Section: Synthesis Of Hs Tetrasaccharidesmentioning
confidence: 99%
“…The biological significance of HS mimics was further evaluated by constructing the HS mimic glycodendrimer D-I21 , as the multivalent display of HS ligands significantly enhances HSBP activity. The glycodendrimers were synthesized by the reaction of the I-21 amine linker with the active carboxylic acid ester of the star dendrimer. The desired glycodendrimer was purified by centrifugation with a 3 kDa ultrafiltration device.…”
Section: Results and Discussionmentioning
confidence: 99%
“…18 The microarray results suggested that sulfated oligo-iduronic acid shows sulfation patterns and oligosaccharide chain length-dependent binding, with growth factors. 19 Specifically, sulfated oligo-iduronic acid ligands I34 show preferential binding with HB-EGF, fibroblast growth factor 2 (FGF2), and amphiregulin. Although the microarrays revealed preferential binding, they did not provide quantification data.…”
mentioning
confidence: 99%